Predictors of Cigarette Smoking Initiation in Early, Middle, and Late Adolescence - O’Loughlin, Jennifer (J Adolesc Health, 2017)
PURPOSE: Little is known about age-related differences in risk factors for cigarette smoking initiation. We identified predictors of initiation in early, middle, and late adolescence from among sociodemographic factors, indicators of smoking in the social environment, psychological characteristics, lifestyle indicators, and perceived need for cigarettes. METHODS: Data were drawn from a longitudinal study of 1,801 children recruited at age 10–11 years from 29 elementary schools in Montreal, Canada. Multivariable logistic regression within a generalized estimating equations framework was used to identify predictors among never smokers across three 2-year windows: age 11–13 years (n = 1,221); age 13–15 years (n = 737); and age 15–17 years (n = 690). RESULTS: Among the 18 risk factors investigated, two differed across age. Friends’ smoking, a strong risk factor in early adolescence (odds ratio [95% confidence interval] = 5.78 [3.90–8.58]), lost potency in late adolescence (1.83 [1.31–2.57]). Depressive symptoms, a risk factor in early and middle adolescence (1.60 [1.26–2.02] and 1.92 [1.45–2.54], respectively), were inversely associated in late adolescence (.76 [.58–1.00]). Sex, TV viewing, and weight-related goals were not associated with initiation at any age. All other factors were significant in two or three age groups. CONCLUSIONS: Most risk factors for smoking initiation were stable across age. Tobacco control interventions may be robust for risk factors across age groups and may not need adjustment. At all ages, interventions should focus on eliminating smoking in the social environment and on reducing the availability of tobacco products.